Planning and Implementation of Hybrid Event Case Study: Muslim Fashion Festival (MUFFEST), March 18-28, 2021 in Jakarta - Fetty Nurmala Rossi; I Made Adhi Gunadi; Hasnah Amirah Kirana (Pusaka : Journal of Tourism, Hospitality, Travel and Business Event, 2022)
This study aims to analyze the planning and implementation of Hybrid Event in Jakarta "Muslim Fashion Festival (MUFFEST) 2021" in Kota Kasablanka Mall and to identify the hybrid elements used during the event. This research method uses qualitative descriptive with a case study approach. Sources of data are obtained through observations with field notes, interviews, and documentation. Data collection techniques used in this study are: interviews with key informants such as Organizer, Supplier, and Venue. Also, literature study was used for qualitative data. This study indicates that the planning and implementation of the event has met all the required aspects. In the hybrid element, this event is also broadcast via live streaming on YouTube, Zoom, Instagram, and the V-Mix application. This study recommends incorporating hybrid elements, such as applications that support virtual exhibition activities and examine the experience of visitors attending the Hybrid Event..